Edukacja retoryczna jako element kształtowania mądrości politycznej - Mathiesen, Aleksandra (ETHICS IN PROGRESS, 2016)
The revolutionary concept of rhetoric introduced by Plato not only stood firmly against the oratorical practices of his times, but also established first “scientific” art of rhetoric applicable into the frames of philosophical paideia. His perception of rhetorical tasks was strictly related to the goals of political formation and was absolutely indispensable for the purposes of a pursuit of political wisdom, in its exceedingly distinctive meaning. Plato initiated a century-long dispute on rhetorical ends and its political - paideutic value. First, criticized by Isocrates, later, resumed in the most exceptional treatise of Aristotle, he delineated a path of a new display of educational value of the art of rhetoric.